(untitled) - Nelson, Alyse (San Francisco, 2012)
The book focuses on the key elements of the Vital Voices Global Partnership organization's five-step model of transformational leadership, including how to find a voice, lead with purpose, cross lines that divide, and more. Through the firsthand accounts of trail-blazing leaders, this book introduces women who are shaping our world.
Keywords: Women,Phụ nữ; Political activity,Hoạt động chính trị